Experimental Modal Analysis of Brake Squeal Noise - Hassan, Muhammad Zahir (2005)
Disc Brake Squeal noise continues to be the major problem concern for the automotive industry. In this paper, the brake squeal phenomenon of brake rotor disc had been investigated using experimental modal analysis (EMA). The modal analysis excitation technique known as impact hammer test has been carried out to obtain modal parameter of brake disc structure namely the natural frequencies of the brake disc. Through the use of accelerometers, it is possible to measure up to four natural frequencies modes associated to the disc brake rotor. This technique can be used to verify the natural frequency obtained from the finite element modelling to validate the computational modelling since the measurements were taken on the true structure of disc brake.